2013
DOI: 10.1103/physrevlett.110.087208
|View full text |Cite
|
Sign up to set email alerts
|

Velocity of the High-Spin Low-Spin Interface Inside the Thermal Hysteresis Loop of a Spin-Crossover Crystal, via Photothermal Control of the Interface Motion

Abstract: We investigated by optical microscopy the thermal transition of the spin-crossover dinuclear iron(II) compound [(Fe(NCSe)(py)(2))(2)(m-bpypz)]. In a high-quality crystal the high-spin (HS) low-spin (LS) thermal transition took place with a sizable hysteresis, at ~108 K and ~116 K on cooling and heating, respectively, through the growth of a single macroscopic domain with a straight LS and HS interface. The interface orientation was almost constant and its propagation velocity was close to ~6 and 26 μ m s(-1) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 19 publications
6
109
1
Order By: Relevance
“…These results were obtained, either in the framework of Molecular Dynamics approaches 13 or using Monte Carlo Arrhenius, 25 Metropolis dynamics, 26 as well as by combining Molecular Dynamics and Monte Carlo method. 27 This general behavior was also supported by simple energetic considerations. 27,28 It has also been shown that in the framework of elastic models with Molecular Dynamics, 13 the nucleation is a macroscopic process, with the size of the critical nucleus proportional to the total system size 29 and the importance of the shape effects has been underlined.…”
Section: Introductionmentioning
confidence: 50%
See 4 more Smart Citations
“…These results were obtained, either in the framework of Molecular Dynamics approaches 13 or using Monte Carlo Arrhenius, 25 Metropolis dynamics, 26 as well as by combining Molecular Dynamics and Monte Carlo method. 27 This general behavior was also supported by simple energetic considerations. 27,28 It has also been shown that in the framework of elastic models with Molecular Dynamics, 13 the nucleation is a macroscopic process, with the size of the critical nucleus proportional to the total system size 29 and the importance of the shape effects has been underlined.…”
Section: Introductionmentioning
confidence: 50%
“…27 This general behavior was also supported by simple energetic considerations. 27,28 It has also been shown that in the framework of elastic models with Molecular Dynamics, 13 the nucleation is a macroscopic process, with the size of the critical nucleus proportional to the total system size 29 and the importance of the shape effects has been underlined.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations